Advancements in astronomy education research: Two decades of progress with undergraduate and adult learners - Molly N. Simon; Janelle M. Bailey (Physical Review Physics Education Research)
In 2003, Bailey and Slater [A review of astronomy education research, Astron. Educ. Rev. 2, 20 (2003)1539-151510.3847/AER2003015] published a review of astronomy education research (AER) to survey the field, identify areas of robust coverage, and uncover gaps in the research to help guide future researchers. While our review is not intended as a direct comparison to their original work, we aim to update the field’s progress since that time. After initially considering more than 450 works, primarily peer-reviewed publications, we focused on research conducted in undergraduate settings or related to non-K-12-teaching adults, such as planetarium professionals, participants in massive open online courses, and citizen scientists. We identified seven broad categories of research, continuing several categories from the original study, such as student understanding and efficacy of instructional strategies, while also introducing new topics, such as authentic research experiences. These findings demonstrate the evolution of AER over the past two decades. The largest body of research remains focused on the efficacy and implementation of instructional strategies. Progress has also been made in exploring technology use (e.g., simulations) in introductory astronomy classrooms and integrating active learning into fully online courses. Notably, course-based undergraduate research experiences have emerged as a new focus in AER. Moving forward, future research should better incorporate educational theory (e.g., mechanisms of learning) and explore the unique educational opportunities offered within astronomy.